PENGARUH MOTIVASI TERHADAP SEMANGAT KERJA PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Taliu, Erni (PREDIKSI, 2016)
This research aims to find out whether there is a positive influence between the motivation against the spirit of employees in Dinas Pekerjaan umum Kabupaten East Kutai. The population in this research is all the employees in Dinas Pekerjaan umum Kabupaten Kutai Timur numbered as many as 40 (forty) employees made as research respondents, in other words this research using the census method.The aim of the research based on the above statement, the analysis of the data used a correlation Coefficient Product Moment (Pearson). The results of the analysis shows that there is a positive influence between the motivation against the Spirit of employees in Dinas Pekerjaan umum Kabupaten East Kutai. This is based on the results of the calculation which stated that the r count greater than r table namely 0, 2501 > 0,312. For critical value on n = 40 with equal significance = 0.05 thus both variables have positive relationships.After r count acquired, then the author testing by using the test t. this hypothesis, value t count is greater than the value of the t table with equal any 0.05 to n - 2 = 38, namely 5,849 > 1,686 or in other words that the motivation to have a positive effect on the spirit of employees work.